(untitled) (Advancements in Homeopathic Research, 2022)
We should keenly take interest and get aware that there is much more in the Organon of Medicine to be discovered as we grow in our understanding & Chronic diseases by Hahnemann. Dr. Kent who was a convert to Homoeopathy when his second wife was cured of paralysis by Dr. Richard A. Phelan., MD, a Homoeopath (6). He resigned his position at the Eclectic College. He began to study and understood Hahnemann’s Homoeopathy very well. In 1890, he founded the Post-Graduate School of Homoeopathy, in /at Philadelphia. At his clinic he treated nearly 40,000 patients (but figure was 42,000 and more). I was madly interested about these cases after reading his book (5), in which many cases were/ are given as examples in; New Remedies, Clinical Cases, Lesser Writings etc, by Dr. Kent J.T., and went to U.S.A, 10 times in search for these cases and enquiries were made to most of the Homoeopaths including Dr. A.H. Grimmer, whom I met in 1962 and discussed about these cases and whereabouts of these cases. He was a long time assistant to Dr. Kent. Where ever in U.S.A. Kent Homes were there, I went and I search his Homes, including basements but all was futile. A treasure of life time experience of Dr. Kent is lost forever. With such sad experience, I started preserving my cases with permanent plastic folder and each case was given a number. Whenever I want to refer any case I can take easily such case.